Loricaria luciae, a new species of whiptail catfish (Siluriformes: Loricariidae) from the Paraguay and lower Paraná River basins of southeastern South America - Thomas, Matthew R.; Rodriguez, Mónica S.; Cavallaro, Marcel R.; Froehlich, Otávio; Castro, Ricardo Macedo Corrêa E (Zootaxa, 2013)
Loricaria luciae, new species, is described from the the rio Paraguay basin of Bolivia, Brazil, and Paraguay, south to its confluence with the rio Paraná in Argentina. It is distinguished from all congeners by the following combination of characteristics: pectoral girdle entirely naked or with small isolated plates near base of pectoral fin, post-ural plate at base of caudal fin large (plate length 17.0–20.3% HL), and total lateral plates 32–33 (modally 32). The new species occurs in a variety of habitats ranging from small, seasonally intermittent streams with clear water to large, turbid rivers over sand and mud substrates. It is sympatric with at least three other species of Loricaria in the Paraguay and lower Paraná drainages, including L. apeltogaster Boulenger 1895, L. coximensis Rodriguez et al. 2012, and L. simillima Regan 1904.